A Review of Islamic Credit Card Using Bay’al-‘inah and Tawarruq Instrument as Adopted by Some Malaysian Financial Institution - Mohd Noor, A.; Azli, R. (Universiti Sains Islam Malaysia, 2024)
Islamic credit card or better known as Credit Card-i is one of the alternative banking products introduced by Islamic financial institutions in Malaysia to substitute the conventional credit card. This paper aims at reviewing the bay’al-‘inah and tawarruq structure as applied by Islamic Financial Institutions in Malaysia from Shariah Compliance perspectives. The method used is descriptive and positive analytical criticism which aims at improving the existing structure.